2011
DOI: 10.3324/haematol.2010.036848
|View full text |Cite
|
Sign up to set email alerts
|

An apparently silent nucleotide substitution (c.7056C>T) in the von Willebrand factor gene is responsible for type 1 von Willebrand disease

Abstract: BackgroundNucleotide variations not changing protein sequences are considered silent mutations; accumulating data suggest that they can, however, be important in human diseases. Design and MethodsWe report an altered splicing process induced by a silent substitution (c.7056C>T) in the von Willebrand factor gene in a case of type 1 von Willebrand disease originally classified as lacking von Willebrand factor mutations. ResultsThe c.7056C>T synonymous substitution introduces a new donor splice site within exon 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…17,18 Heterozygotes for type 2N VWF are considered carriers of the defect, like haemophilia A carriers, and they are mostly asymptomatic.…”
mentioning
confidence: 99%
“…17,18 Heterozygotes for type 2N VWF are considered carriers of the defect, like haemophilia A carriers, and they are mostly asymptomatic.…”
mentioning
confidence: 99%
“…It is now recognized from large studies of families with VWD that, in addition to characterized VWD mutations, several polymorphisms modify VWF levels and may modify VWF activity. 13,[26][27][28] We therefore measured the levels of mutant and normal VWF mRNA in affected and unaffected members of the pedigree to investigate the potential contribution of a hypomorphic normal allele to the observed phenotypic variability. The levels of the normal mRNA were similar among the affected individuals carrying the M1304R variant, ranging from 73% to 78% of total VWF mRNA, ruling out a contribution of a hypomorphic allele (supplemental Figure 2).…”
Section: Increased Incorporation Of Wild-type Monomers Improves Vwf Smentioning
confidence: 99%
“…The mutation results in p.Gly2352_Cys2360del in the B2 domain. 11 This study highlights that mutations could be overlooked during standard VWF molecular analysis because they are perceived as being not disease-causative. Notably, the c.7056C>T mutation was previously observed in the Canadian type 1 VWD study, but was reported as a polymorphism.…”
Section: Novel Mutations Previously Overlooked In Von Willebrand Diseasementioning
confidence: 99%
“…In this issue of the journal, Daidone et al 11 highlight a mutation previously overlooked in VWF molecular analysis. The authors analyzed all 52 exons, flanking intronic sequence and the 5' and 3' untranslated regions of VWF in a family diagnosed with mild-moderate type 1 VWD.…”
Section: Novel Mutations Previously Overlooked In Von Willebrand Diseasementioning
confidence: 99%